Conversion of Palm Cooking Oil to Bio-Plasticizer by Sulfuric Acid Catalyzed - Hendriyana, Hendriyana; Andini Hizbiyati (Universitas Negeri Semarang, 2025)
The increasing environmental and health concerns associated with conventional phthalate-based plasticizers have driven research toward sustainable alternatives. This study investigates the epoxidation of palm cooking oil (PCO) using sulfuric acid as a catalyst to produce epoxidized palm cooking oil (EPCO) as a bio-based plasticizer. The epoxidation process was conducted at various temperatures and catalyst concentrations to evaluate their effects on iodine value, double bond conversion, and viscosity. Optimal epoxidation was achieved at 50 °C and 1 wt% sulfuric acid, resulting in an iodine value of 1.86 g I₂/100 g and a C=C conversion rate of 65.53%. FTIR spectroscopy confirmed the successful formation of oxirane rings, as evidenced by the appearance of C–O–C stretching peaks. The epoxidized product exhibited increased viscosity and density, indicating successful structural modification. Furthermore, blending tests with PVC showed good miscibility and plasticizing performance, supporting EPCO’s potential application as a renewable, non-toxic plasticizer in polymer processing.